2010
DOI: 10.1029/2010ja015784
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the nighttime thermospheric mass density at low and middle latitudes

Abstract: [1] The latitudinal structure of the nighttime thermospheric mass density at 385 km has been investigated using observations made by the accelerometer onboard the CHAMP satellite between 2002 and 2007. The nighttime thermospheric mass density had a clear latitudinal variation. There was a local density peak around the geographic equator and two minima at about ±30°. This nighttime equatorial mass anomaly (NEMA) was opposite to the latitudinal variations of the daytime ionospheric equatorial anomaly and thermos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 46 publications
5
40
0
Order By: Relevance
“…Ruan et al (2014) reported occurrence of the MDM in upper thermospheric CHAMP data within 20° of the equator, with extension to southern midlatitudes during solar minimum. Ma et al (2010) studied the nighttime EMA (NEMA) in CHAMP data and found that the equatorial density enhancements peaked near 02 LT; this suggests that the MDM and NEMA are either the same feature or are closely related. Akmaev et al (2009Akmaev et al ( , 2010 showed via WAM simulations that the MDM is closely connected to tides, especially the migrating terdiurnal tide and higher harmonics propagating from the lower atmosphere.…”
Section: Midnight Density Maximummentioning
confidence: 95%
See 1 more Smart Citation
“…Ruan et al (2014) reported occurrence of the MDM in upper thermospheric CHAMP data within 20° of the equator, with extension to southern midlatitudes during solar minimum. Ma et al (2010) studied the nighttime EMA (NEMA) in CHAMP data and found that the equatorial density enhancements peaked near 02 LT; this suggests that the MDM and NEMA are either the same feature or are closely related. Akmaev et al (2009Akmaev et al ( , 2010 showed via WAM simulations that the MDM is closely connected to tides, especially the migrating terdiurnal tide and higher harmonics propagating from the lower atmosphere.…”
Section: Midnight Density Maximummentioning
confidence: 95%
“…They additionally reported that the EMA shows a strong response to geomagnetic activity. Ma et al (2010) studied the latitudinal dependence of CHAMP data in the nighttime sector; here, the density peaks at the geographic equator, with minima at ±30° latitude. They called this feature the nighttime EMA (NEMA).…”
Section: Equatorial Density Anomalymentioning
confidence: 99%
“…It is possible that the effects of these waves may be disproportionately important in this case as waves seem to be relatively more important at solar minimum (for example, Ma et al [2010] showed that the midnight temperature maximum was more prominent at solar minimum).…”
Section: The Causes Of Temperature Variations In the Low And Middle Lmentioning
confidence: 99%
“…Nevertheless, their application to thermosphere studies has resulted in density and wind data sets containing information at unprecedented levels of detail and coverage. Analyses of accelerometer-derived density data sets resulted in the publication of a large number of scientific papers, on topics including the response to drivers such as solar EUV variability [Guo et al, 2007;Müller et al, 2009], geomagnetic activity and storms Sutton et al, 2005;Burke et al, 2009;Lathuillère et al, 2008;Lathuillère and Menvielle, 2010;, substorms , Joule heating , solar flares [Liu et al, 2007b], solar wind streams [Lei et al, 2008]; and on phenomena such as the equatorial mass density anomaly Ma et al, 2010], medium-to large-scale variability , upwelling in the cusp region [Lühr et al, 2004;Rentz and Lühr, 2008], travelling atmospheric disturbances Forbes, 2007, 2009], solar terminator waves Liu et al, 2009;Miyoshi et al, 2009], atmospheric tides Oberheide et al, 2009] and wave structures at solar minimum [Bruinsma and Forbes, 2010]. These investigations generally made use of density data processed using algorithms published by Bruinsma and Biancale Investigations of wind results from the CHAMP mission have started to appear in recent years as well.…”
Section: Density and Crosswind From Accelerometer Datamentioning
confidence: 99%